Continuous Mapping Identifies Loci Associated With Weevil Resistance [Cosmopolites sordidus (Germar)] in a Triploid Banana Population - Uwimana, Brigitte; Mwanje, Gerald; Batte, Michael; Akech, Violet; Shah, Trushar; Vuylsteke, Marnik; Swennen, Rony (Frontiers in Plant Science, 2021)
The first step towards marker-assisted selection is linking the phenotypes to molecular markers through quantitative trait loci (QTL) analysis. While the process is straightforward with self-pollinating diploid species, QTL analysis in polyploids requires unconventional methods. In this study, we have identified markers associated with weevil Cosmopolites sordidus (Germar) resistance in banana using 138 triploid (2n = 3x) hybrids derived from a cross between a tetraploid ‘Monyet’ (2n = 4x) and a diploid ‘Kokopo’ (2n = 2x) banana genotypes. The population was genotyped by DArTSeq, resulting in 18,009 polymorphic SNPs between the two parents. Marker–trait association was carried out by continuous mapping where the adjusted trait means for corm peripheral damage (PD) and total cross-section damage (TXD), both on the logit-scale, were regressed on the marker allele frequencies. Forty-four SNPs were identified that were associated with corm peripheral damage on the chromosomes 5, 6, and 8 with 41 of them located on chromosome 6 and segregating in ‘Kokopo’. Eleven SNPs associated with corm total cross-section damage were identified on chromosome 6 and segregating in ‘Monyet’. The additive effect of replacing one reference allele with the alternative allele was determined at each marker position. The peripheral damage QTL was confirmed using conventional QTL linkage analysis in the simplex markers segregating in ‘Kokopo’ (RRRR x RA). We also identified 43 putative genes in the vicinity of the markers significantly associated with the two traits. The identified loci associated with resistance to weevil damage will be used in the efforts of developing molecular tools for marker-assisted breeding in banana.